Population genetic structure of Brycon henni fish (Characiformes: Characidae) in the Andean region of Colombia using microsatellite molecular markers - Muñoz, Luz Elena (2019)
Fish species in Colombian Andes are subject to processes of overfishing, exotic species invasions, habitat loss, ecosystems fragmentation and low connectivity that limits the genetic flow and leads populations to loss genetic variability and extinction. Genetic variation of B. henni from four basins of the Colombian Andean region (Risaralda, Campoalegre, Riofrío and Chinchiná) was analyzed using ten microsatellites in 60 samples. A total of 136 alleles were found. Except BoM12, all markers were highly informative and polymorphic and presented a significant deviation (P < 0.05) from Hardy Weinberg Equilibrium. There was a marked deficiency of heterozygotes (FIS = 0.526). In Campoalegre river basin, the largest allele number, average allele number and private alleles were observed (81, eight and 34 alleles, respectively) and HE 0.689 ± 0.05. Moderate and highly significant genetic structure was evidenced (FST = 0.07). According to the standard distance of Nei (1972), population from Campoalegre River basin was the most divergent. This results suggest that genetic variability of the B. henni in the studied basins may be affected by critical low population density, river pollution and overfishing.